2008
DOI: 10.1016/j.str.2008.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Recognition of the H3K4me3 Mark by the TFIID Subunit TAF3

Abstract: Trimethylation of lysine residue K4 of histone H3 (H3K4me3) strongly correlates with active promoters for RNA polymerase II-transcribed genes. Several reader proteins, including the basal transcription factor TFIID, for this nucleosomal mark have been identified. Its TAF3 subunit specifically binds the H3K4me3 mark via its conserved plant homeodomain (PHD) finger. Here, we report the solution structure of the TAF3-PHD finger and its complex with an H3K4me3 peptide. Using a combination of NMR, mutagenesis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 56 publications
11
120
0
Order By: Relevance
“…It is interesting to note that the methylation of H3K4 has been related with the transcriptional activation of genes and is a strong predictor for RNA pol II promoters. In particular, the trimethylated form of H3K4 has been found primarily around the transcription start sites of active genes (van Ingen et al, 2008) as in our case.…”
Section: Post Translational Modifications (Ptms) and Pltalpha2 Gene Asupporting
confidence: 69%
“…It is interesting to note that the methylation of H3K4 has been related with the transcriptional activation of genes and is a strong predictor for RNA pol II promoters. In particular, the trimethylated form of H3K4 has been found primarily around the transcription start sites of active genes (van Ingen et al, 2008) as in our case.…”
Section: Post Translational Modifications (Ptms) and Pltalpha2 Gene Asupporting
confidence: 69%
“…Based on our findings and studies published to date regarding the role of TAF7 and TAF1 in transient transcriptional repression required for effective PIC assembly (28), we suggest that the TAF1/7 complex could read the repressive H3K27me3 mark to help induce this temporary transcriptional arrest and that subsequent H3S28 phosphorylation could reverse this effect to induce transcription initiation. It will also be interesting to see if TAF1/7 plays a role in recognition of bivalent chromatin in embryonic stem cells, which contains both the repressive H3K27me3 mark and an active H3K4me3 mark, and in cross-talk with the TAF3-PHD domain that recognizes the H3K4me3 mark on genes that are marked with bivalent chromatin (6,(29)(30)(31). Further experiments would be required to test these, and other, possibilities, but our findings will provide a strong structural basis for future studies of the possible regulatory interplay between the TAF1/7 complex and H3K27me3/H3S28ph switch in transcription initiation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, TFIID can behave as an epigenetic effector, capable of recognizing posttranslational histone modifications associated with activated transcription. Eukaryotic TAF1 contains a double bromodomain that recognizes acetylated histones, and TAF3 contains a plant homeo domain (PHD) that binds to histone H3 methylated at lysine 4 (5,6). In addition to roles in basal transcription, TFIID is also associated with diseases.…”
mentioning
confidence: 99%
“…This modification counteracts the active transcriptional state by blocking the function of the H3K4 methyltransferase complexes COMPASS in yeast and ASH2/MLL in humans (39). Previously, H3R2me2a was shown to strongly reduce the binding affinity of AIRE-PHD1 to H3K4me0 (26) and of the TAF3-PHD finger to H3K4me3 (40), whereas only a limited effect was observed for the ING2-or BPTF-PHD fingers (30). This suggested that H3R2me2a plays distinct cross-talk roles for different proteins.…”
Section: Volume 286 • Number 42 • October 21 2011mentioning
confidence: 99%